2019
DOI: 10.1111/ced.14086
|View full text |Cite
|
Sign up to set email alerts
|

National audit on the management of bullous pemphigoid

Abstract: Summary Background Bullous pemphigoid (BP) is an autoimmune, subepidermal, blistering condition that typically affects elderly people. Aim To undertake a national clinical audit based on standards derived from the British Association of Dermatologists (BAD) clinical guidelines on the management of BP. Methods In 2018, BAD members were invited to submit data for five consecutive adults with BP per centre, who had been under hospital supervision for at least 12 months, in a national audit over an 11‐week period.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 6 publications
0
6
0
Order By: Relevance
“…In line with this, sustained or enhanced serum levels of IL-17 were associated with relapses in BP [93]. Therefore, the marked association between OP and pemphigus can be explained at the molecular level by the immunopathogenic process and by the pro-inflammatory cells and cytokines shared in both disorders that lead to a net increase in bone resorption [92]. The guidelines for the treatment of BP of the British Association of Dermatologists recommend topical steroids as the first line of treatment if the pathology is limited; in the case of generalized pathology, the first line to be considered are topical steroids or high doses of systemic cortisone, while immunosuppressants (methotrexate, mycophenolate mofetil, azathioprine and dapsone) are to be considered the second line of treatment in extensive pathology, in patients who do not respond to oral corticosteroids or who have contraindications to it [92].…”
Section: Blistering Diseasementioning
confidence: 56%
See 2 more Smart Citations
“…In line with this, sustained or enhanced serum levels of IL-17 were associated with relapses in BP [93]. Therefore, the marked association between OP and pemphigus can be explained at the molecular level by the immunopathogenic process and by the pro-inflammatory cells and cytokines shared in both disorders that lead to a net increase in bone resorption [92]. The guidelines for the treatment of BP of the British Association of Dermatologists recommend topical steroids as the first line of treatment if the pathology is limited; in the case of generalized pathology, the first line to be considered are topical steroids or high doses of systemic cortisone, while immunosuppressants (methotrexate, mycophenolate mofetil, azathioprine and dapsone) are to be considered the second line of treatment in extensive pathology, in patients who do not respond to oral corticosteroids or who have contraindications to it [92].…”
Section: Blistering Diseasementioning
confidence: 56%
“…These considerations led the authors to argue that these dermatological patients may benefit from increased screening for OP and interventions to prevent fractures [91]. Pemphigus is an autoimmune disease dependent on T cells principally of self-reactive Th2 cells, which also involves pro-inflammatory cytokines of the innate immune system, such as TNF, IL-1, and IL-6 [92]. Moreover, Le Jan et al [93] identified IL-17 and related cytokines such as IL-22 and IL-23 in the serum and blister fluids of BP patients; these cytokines may lead to a feedback loop and the perpetuation of the autoinflammatory process increasing MMP-9 secretion and CXCL10 expression from leukocyte cells [94].…”
Section: Blistering Diseasementioning
confidence: 99%
See 1 more Smart Citation
“…In this, 85.5% (448 of 524) of those with bullous pemphigoid diagnoses were prescribed an oral corticosteroid by their dermatologist at some point during their management. (22) We report that a more modest 69.6% of people are prescribed prednisolone in primary care, although this discrepancy may be largely attributed to the different settings. The higher proportion from the survey suggests that some people are exposed to prednisolone only in secondary, and not primary, care.…”
Section: Comparison With Existing Literaturementioning
confidence: 70%
“…The benchmark diagnoses may be subject to misclassification bias due to a heterogeneous group of pemphigoid variants (eg, non-bullous pemphigoid, which presents with intense itching, a polymorphic rash, but no blisters), alternative approaches to making a diagnosis and differences in the diagnostic tests used to confirm the diagnosis. 22 23 Nevertheless, this was regarded as the best approach as external validation with hospital notes was not possible. Finally, validation was only possible for a third of patients and it may be that patients with a hospitalisation record for a blistering disease are not representative of the overall population of patients as they are more likely to have severe disease and associated comorbidities.…”
Section: Discussionmentioning
confidence: 99%